2012
DOI: 10.1002/app.38893
|View full text |Cite
|
Sign up to set email alerts
|

A water‐soluble acrylamide hydrophobically associating polymer: Synthesis, characterization, and properties as EOR chemical

Abstract: A water-soluble acrylamide hydrophobically associating terpolymer for polymer flooding was successfully synthesized via free radical polymerization using acrylamide (AM), acrylic acid (AA), and N,N-divinylnonadeca-1,10-dien-2-amine (DNDA) as raw materials. The terpolymer was characterized by IR spectroscopy and fluorescence spectra. Compared with partially hydrolyzed polyacryamide (HPAM), the terpolymer showed a stronger link and better dimensional network structure under the environmental scanning electron mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 29 publications
2
44
0
Order By: Relevance
“…The salt resistance was investigated by using 1000 mg/L of ANOB solution at 25 °C compared with HPAM. It can be found that the viscosity of HPAM solution tends to drop linearly with the increase of NaCl concentration (Figure 7), as reported by others [1,10] . For ANOB, the solution viscosity quickly decreases with increasing NaCl concentration up to 6000 mg/L, and then keeps smooth.…”
Section: Effect Of Nacl On Viscositysupporting
confidence: 74%
See 2 more Smart Citations
“…The salt resistance was investigated by using 1000 mg/L of ANOB solution at 25 °C compared with HPAM. It can be found that the viscosity of HPAM solution tends to drop linearly with the increase of NaCl concentration (Figure 7), as reported by others [1,10] . For ANOB, the solution viscosity quickly decreases with increasing NaCl concentration up to 6000 mg/L, and then keeps smooth.…”
Section: Effect Of Nacl On Viscositysupporting
confidence: 74%
“…In general, the viscosity of polymer solution is strongly dependent on temperature. [1,10] When temperature increases, the intermolecular interaction decreases due to the increase in thermal motion of molecules. At high temperature, the viscosity of polymer solution may decrease because of weak bond in polymer chemical structure, leading to the breakage of hydrophobic side chain from polymer backbone.…”
Section: Effect Of Temperature On Viscositymentioning
confidence: 99%
See 1 more Smart Citation
“…With the temperature increase, a large number of associating groups aggregated together to form reversible, physical, supermolecular structures by strong van der Waal's interactions. 30 The introduction of the benzene ring in the hydrophobic monomer can also improve the associating properties and temperature tolerance of DTHAP. However, the supermolecular structure formed by hydrophobic association was unstable, especially under high temperature, which resulted in the decrease of viscosity.…”
Section: The Optimization Of the Synthesis Conditionsmentioning
confidence: 99%
“…Because more compact three dimension network structure can be observed directly from the ESEM images of HAP than HPAM. 18,30 The DTHAP solutions (DTHAP concentration, 2 g/ L) for ESEM were prepared by smearing a small amount of DTHAP solutions on conducting resin. Then, the samples were dried by Vacuum Freezing and Drying Technology before observation.…”
Section: Environmental Scanning Electron Microscope (Esem) Imagesmentioning
confidence: 99%